Intemporal Capital Assets Pricing Model Sebagai Prediktor Return Portofolio Saham - Amaroh, Siti (Jurnal Ilmiah Aset, 2009)
This study has purpose to examine Capital Assets Pricing Model (CAPM) and Fama-French Model for firms listed on Indonesia Stock Exchange for the period 1992-2000 both in up market and down market using all nonfinancial and banking firms. The result shows that portfolio returns are affected by market factor, excess return on portfolio constructed by size (Small Minus Big, SMB), and excess return on portfolio constructed by book-to-market ratio (High Minus Low, HML). Market factor positively affects portfolio return in all monthly test and in down market, but not significant in up market. Return differences of portfolio constructed by size is also positively affects on small stock portfolio return for all monthly tests and down market. Return differences of portfolio constructed by book-to-market ratio is positively affects on portfolio return for all monthly test both in up and down market.